The effect of increased pork hot carcass weights on loin quality, consumer appearance and purchase intent ratings, and palatability ratings of top loin chops - Rice, Emily Ashton (Kansas State University, 2019)
The objective of this study was to evaluate the effect of increased pork hot carcass weights on consumer palatability and visual acceptability and purchase intent of top loin chops cut to various thicknesses in a price labeled versus unlabeled retail display scenario. Pork loins (N = 200) were collected from 4 different hot carcass weight groups: light (LT; less than 111.8 kg), medium-light (MLT; 111.8 to 119.1 kg), medium-heavy (MHVY; 119.1 to 124.4 kg), and heavy (HVY; 124.4 kg and greater). Loins were fabricated into 4 pairs of chops of specified thicknesses ( cm). One chop from each specified thickness was then randomly assigned to be packaged with or without a label. Consumers assessed chops from each weight group × thickness combination in both labeled and unlabeled scenarios. Chops were assessed on a continuous line scale for desirability and purchase intent. After visual evaluation, chops were vacuum packaged and frozen at 10-days postmortem. Chops were then reallocated so that one chop from each loin was assigned to consumer sensory panels and one chop was assigned to trained sensory panels. For visual ratings there was a hot carcass weight × chop thickness interaction (P < 0.05) for the percentage of consumers who answered “yes” that the chop was desirable. Within all weight treatments, the lowest (P < 0.05) percentage of consumers indicated chops with a thickness of 1.27 cm were desirable. Both appearance and purchase intent ratings increased as hot carcass weight increased. Chops with a thickness of 2.54 and 3.18 cm had the greatest (P < 0.05) appearance ratings. Additionally, 1.27 cm thick chops had both the lowest (P < 0.05) purchase intent ratings, and the lowest (P < 0.05) percentage of consumers who would purchase them. For palatability ratings, consumer found chops from heavier carcasses to be more (P < 0.05) acceptable for juiciness and tenderness. Additionally, consumers gave chops from the LT hot carcass weight treatment the lowest (P < 0.05) tenderness ratings. Chops from the HVY and MHVY weight treatment groups were similar (P > 0.05) but had the greatest (P < 0.05) consumer overall like ratings. Trained panelists gave similar results with chops from the HVY and MHVY hot carcass weight group receiving greater (P < 0.05) initial and sustained juiciness ratings compared to chops from lighter carcasses. Additionally, chops form HVY and MHVY carcasses were similar (P > 0.05) and had greater (P < 0.05) overall tenderness ratings compared to chops form LT carcasses from trained panelists. These results indicated that hot carcass weight and chop thickness can impact consumer purchasing decisions in a retail setting. Additionally, as hot carcass weight increased both tenderness and juiciness palatability characteristics.
Keywords: Consumer preference; Heavy weight pigs; Hot carcass weight; Palatability; Pork quality; Visual